Answer : Explanation : This can be solved in two ways using only 6, 11, 9 and 3 we must get 24.1. {[(11–6) x 3] 9}By solving this we get5 x 3 9 = 15 9 = 24. 2. [(9–6) x (11–3)]= 3 x 8 = 24.

**Click here to see the full blog post**

**last edited by**

How can we get 24 as an answer by using 6, 11, 3 and 9?

Answer : Explanation : This can be solved in two ways using only 6, 11, 9 and 3 we must get 24.1. {[(11–6) x 3] 9}By solving this we get5 x 3 9 = 15 9 = 24. 2. [(9–6) x (11–3)]= 3 x 8 = 24.

**Click here to see the full blog post**